Population predictors of community health and social service use in Northern Ireland. Issue 6 (December 1997) - Warnes, A M; Armstrong, G K; Peters, D
Abstract : STUDY OBJECTIVE: To investigate the characteristics of elderly populations associated with variations in their use of community health and personal social services and to test the hypotheses that the variations are related to: (a) the age structure of an elderly population; (b) the population's socioeconomic composition, including the level of deprivation; and (c) household or living arrangements. DESIGN: A common file of 1991 population census and 1994 NHS community trust operational variables was constructed for 67 postcode sectors, with the independent variables describing the age-sex groups to be studied. Clear criteria for the exclusion of "empty" sectors were developed. Relationships using bivariate and multivariate correlation and stepwise multiple regression were explored. SETTING: Eastern Health and Social Services Board area, Northern Ireland (Belfast and hinterland). PARTICIPANTS: Population of statutory pensionable age; in aggregate, younger and older age bands. MAIN RESULTS: The age structure or mean age of the elderly population had only a weak association with the community health and social service client rate, but there were strong associations with socio-economic variables, particularly the percentage of those living alone who were without a car and the percentage of pensioner households that included an adult of below pensionable age. Parsimonious multiple regression models accounted for between 46% and 80% of the variation in the NHS community trust client rate. Greater explanations were achieved for the young elderly population than for those aged 75+ years and, when the population was divided between young and old age bands, for men than for women. CONCLUSIONS: Community health and social services for elderly people in eastern Northern Ireland were focused on those with a low income and those who were not co-resident with adults of working age. When local elderly populations are compared, per capita morbidity and dependency are often higher where the mean age is low, and vice versa, because of the inverse relationship between socioeconomic status and survival in old age. Capitation scales for resource allocation with positive age weighting will be of little use if no account is taken of the relative prevalence of need in the youngest or base age group.